3
$\begingroup$

In the Lorentz transformation of the field $\partial_\mu\phi(x)$ (Peskin, p.36)

\begin{eqnarray} \partial_\mu\phi(x)\to\partial_\mu(\phi(\Lambda^{-1}x))=(\Lambda^{-1})^\nu_{\phantom{\nu}\mu}(\partial_\nu\phi)(\Lambda^{-1}x), \tag{3.3} \end{eqnarray}

I don't understand how to derive $(\Lambda^{-1})^\nu_{\phantom{\nu}\mu}$ in the r.h.s. and what is difference between $(\partial_\mu\phi)(x)$ and $\partial_\mu(\phi(x))$?

$\endgroup$
3
$\begingroup$

Let's forget about the indices for a while and do the chain rule: $$ \partial_x\left(f(\lambda^{-1} x)\right) =\dfrac{\partial f(\lambda^{-1} x)}{\partial x} =\lambda^{-1}\dfrac{\partial f(\lambda^{-1} x)}{\partial (\lambda^{-1} x)} \quad. $$ This explains the $\Lambda^{-1}$ prefactor on the RHS. If you understand this, adding indices should be pretty straightforward.

The second part of your question is caused by the standard abuse of notation. Again, let's suppress the indices for a moment. Since $$ \dfrac{\partial f(s)}{\partial s} \equiv (\partial_s f)(s) \quad, $$ we can write $$ \dfrac{\partial f(\lambda^{-1} x)}{\partial (\lambda^{-1} x)} = (\partial_s f)(s) \biggr\rvert_{s=\lambda^{-1}x} = f^{\,\prime}(\lambda^{-1}x) \quad. $$

$\partial_\mu(\phi(\Lambda^{-1}x))$ corresponds to the derivative of the function $\tilde{\phi}(x)=\phi(\Lambda^{-1}x)$ with respect to $x^\mu$: $$ \partial_\mu(\phi(\Lambda^{-1}x)) = \dfrac{\partial \tilde{\phi}(x)}{\partial x^\mu} = \dfrac{\partial \phi(\Lambda^{-1}x)}{\partial x^\mu} \quad. $$ $(\partial_\mu\phi)(\Lambda^{-1}x)$ corresponds to calculating the derivative of $\phi(s)$ with respect to $x^{\mu}$, and then evaluating this derivative at the point $s = \Lambda^{-1}x$: $$ (\partial_\mu\phi)(\Lambda^{-1}x) = \left.\dfrac{\partial\phi(s)}{\partial x^\mu}\right|_{s=\Lambda^{-1}x} \quad. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.